Assessment and determinants of airborne bacterial and fungal concentrations in different indoor environments: Homes, child day-care centres, primary schools and elderly care centres - Madureira, J. (2015)
Until now the influence of risk factors resulting from exposure to biological agents in indoor air has been far less studied than outdoor pollution; therefore the uncertainty of health risks, and how to effectively prevent these, remains. This study aimed (i) to quantify airborne cultivable bacterial and fungal concentrations in four different types of indoor environment as well as to identify the recovered fungi; (ii) to assess the impact of outdoor bacterial and fungal concentrations on indoor air; (iii) to investigate the influence of carbon dioxide (CO2), temperature and relative humidity on bacterial and fungal concentrations; and (iv) to estimate bacterial and fungal dose rate for children (3e5 years old and 8e10 years old) in comparison with the elderly. Air samples were collected in 68 homes, 9 child day-care centres, 20 primary schools and 22 elderly care centres, in a total of 264 rooms with a microbiological air sampler and using tryptic soy agar and malt extract agar culture media for bacteria and fungi growth, respectively. For each building, one outdoor representative location were identified and simultaneously studied. The results showed that child day-care centres were the indoor microenvironment with the highest median bacterial and fungal concentrations (3870 CFU/m3 and 415 CFU/m3, respectively), whereas the lowest median concentrations were observed in elderly care centres (222 CFU/m3 and 180 CFU/m3, respectively). Indoor bacterial concentrations were significantly higher than outdoor concentrations (p < 0.05); whereas the indoor/outdoor ratios for the obtained fungal concentrations were approximately around the unit. Indoor CO2 levels were associated with the bacterial concentration, probably due to occupancy and insufficient ventilation. Penicillium and Cladosporium were the most frequently occurring fungi. Children's had two times higher dose rate to biological pollutants when compared to adult individuals. Thus, due to children's susceptibility, special attention should be given to educational settings in order to guarantee their healthy future development.